Preparation of levofloxacin-imprinted nanoparticles using designed deep eutectic solvents for the selective removal of levofloxacin pollutants from environmental waste water. Issue 8 (28th February 2020) - Li, Xiaoxia; Row, Kyung Ho
Abstract : Designed deep eutectic solvents was applied to preparation of levofloxacin-imprinted nanoparticles as functional monomer. The nanoparticles using for the selective removal of levofloxacin pollutants from a natural environmental system. Abstract : A deep eutectic solvent (DES) was prepared from choline chloride (ChCl) and methacrylic acid (MAA) and used as an eco-friendly surfactant and functional monomer. The process of producing DES and its free energy of formation (Δ G = −37.225 kcal mol −1 ) were evaluated theoretically by density-functional theory. The designed DES (ChCl–MAA) was introduced as a novel eco-friendly functional monomer (MAA as the control group) during the preparation of levofloxacin-imprinted nanoparticles (LINs) based on molecular imprinting technology. The nanoparticles were characterized using a range of techniques. The nanoparticles were applied as an adsorbing material to the selective removal of levofloxacin from environmental waste water. The selective removal and adsorption capacity of the adsorbing material were evaluated by high-performance liquid chromatography. Based on the introduction of DES, DES–LINs had better adsorption capacity for levofloxacin than common LINs. This method had the simple operation, rapid adsorption and efficient decontamination.